Motivations behind individuals' energy efficiency investments and daily energy-saving behavior: The case of China - J. K. Perret; V. Udalov; N. Fabisch (International Economics and Economic Policy, 2021)
The impact of environmental motivations on the individual's decisions regarding investments in energy efficiency and the adoption of energy-saving habits are analyzed for a representative sample of Chinese inhabitants from the larger Beijing area, replicating a comparative study on Western Europe. For the considered type of energy efficiency investments and daily energy-saving activities similarities and discrepancies between the two regions are discussed in regard to their sociocultural background as well as governmental regulations. The study provides empirical evidence that for Chinese environmental issues if all only play a tertiary role after monetary and regulatory incentives. The findings could suggest that in China policy programs aimed at raising environmental awareness and forming pro-environmental motivations might not lead to an increase in energy efficiency investments and daily energy-saving activities and the Chinese government's interests in this regard might be better served by implementing corresponding incentives via regulations. In the long-term. However, social peer pressure might affect a change in the Chinese mentality.
Keywords: F64; C26; Z13; 330; Environment; Behavior; Energy efficiency; Energy-saving; Environmental motivation; China; Cross-cultural